PENGGUNAAN MEDIA WORDWALL DALAM MENINGKATKAN KOSAKATA ANAK USIA DINI DI TK LITTLE ABDULLAH SCHOOL CILEGON - Mahdiyah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of Wordwall media has proven to be effective in enhancing the vocabulary of early childhood learners compared to conventional methods. Children who learn with Wordwall demonstrate better ability to recall and use new vocabulary, along with higher levels of engagement and learning interest. These findings highlight the importance of utilizing interactive educational technology such as Wordwall to support vocabulary learning during the early stages of child development.